Marsz Niepodległości, czyli o złożoności i wielowymiarowości tego wydarzenia z perspektywy koncepcji heterotopii Michela Foucaulta - Wolniewicz-Slomka , Klaudia; Czech-Włodarczyk , Celina (Studia Edukacyjne, 2023)
The annual, nationwide “Independence March” taking place on the anniversary of Poland regaining independence has become a phenomenon and the only event of its kind at that time. It brings together – in the physical sense – thousands of Poles. However, it is even more engaging in symbolic terms. The research aimed to analyze the Independence March as a heterotopic space according to Michel Foucault and, more precisely, to refer to four of the six principles of heterotopia proposed by the French philosopher. The first two principles apply to society in general and, therefore, were not analyzed in relation to the event of the Independence March. The remaining four were successfully used to reflect on it more deeply. Research has shown that the “Independence March” is an example of heterotopia, and what distinguishes it from other previously studied spaces with heterotopic features is the simultaneous variability and spatial stability, the range of influence, the multitude of ways of entering its space and the significant function it performs because of its complexity.